The impact of explicit teacher feedback on micro and macro level features of the performance of the EFL students in descriptive writing - Soori, Afshin; Abd. Samad, Arshad; Abu Bakar, Kamariah (Marsland Press, 2011)
Teacher feedback is an essential aspect of any English language writing course. This is especially true now with the predominance of the process approach to writing that requires some kind of second party feedback, usually the instructor, on student drafts. Kroll describes feedback as one of the two components most central to any writing course with the other being assignments the students is given. Although teacher feedback seems an ideal one and most preferred by many students in second language instruction, its fruitfulness in developing students’ writing is not so crystal clear. Moreover, many unanswered questions remain regarding micro and macro level features which have not been adequately attended by researchers. It seems the answers to these questions are not convincing, and there is a gap in this area. So, to fill the gap an investigation should be conducted to inform of whether this leads to improving the students’ overall writing quality.